'Deep understanding' for anti‐racist school transformation: School leaders' professional development in the context of Black Lives Matter. Issue 1 (10th November 2022) - Walker, Sharon; Bennett, Ian; Kettory, Pavenjit; Pike, Clare; Walker, Lee
Abstract: In June 2020, the world witnessed an upsurge in Black Lives Matter (BLM) demonstrations following the murder of George Floyd, an African American, by a White American police officer. The international response called for the global community to reassess the value of black lives blighted by racist social systems. The mass sentiment acted as a catalyst for educational institutions, including those in the UK, to mount a response. It is in this context that a School Partnership Group representing primary and secondary schools in East London embarked on developing a workshop series for the professional development of school leaders. The sessions were aimed at school transformation through anti‐racist educational approaches. In this article, we present a discussion of the workshop series held in the academic year 2020–2021, which brought school leaders together in a reflective community of practice. Drawing on data from focus group conversations carried out following the end of the series, this paper argues for school leaders' professional development that prioritises 'deep understanding' supported by reflective communities of practice as a pre‐requisite for effective anti‐racist practice and sustained school transformation.